The democratic contribution of participatory budgeting - Yves Cabannes; Barbara Lipietz (London School of Economics and Political Science (LSE), Department of International Development, 2015)
Participatory Budgeting (PB) has emerged as one of the major innovations in participatory governance for local management and local democracy worldwide. With more than 3,000 experiences recorded in over forty countries, PB is gradually changing the living conditions of increasing numbers of citizens across the world. Highly heterogeneous in processes and underlying ambitions, PB in its diversity provides a challenging alternative to the New Public Management-informed route to public sector reform. In most cases, PB has positively contributed to administrative modernization and other 'good governance' imperatives, including bringing substance to decentralization policies. In its most radical incarnations, PB has moreover contributed to inversing established spatial, social and political priorities in cities, in favour of the more deprived. This working paper briefly introduces the world-wide expansion of PB and the heterogeneity of current experiences before proposing two analytical frameworks to help differentiate between them. The heterogeneity of cases reflects substantially differing logics which can be described as political (for radical democratic change), managerial and technocratic (to improve municipal finance transparency and optimize the use of public resources for citizens' benefit) or good governance driven (to improve links between the public and citizens spheres). These logics are illustrated through the examples of Rosario (Argentina), Seville (Spain), Chengdu (China), Soligen (Germany), Dondo (Mozambique) and Porto Alegre (the iconic case in Brazil). Finally, the paper closes with an assessment of PB's major contributions to democratic governance, as well as its on-going challenges and limitations to date. Specifically, we bring attention to PB's potential in reverting (political and territorial) priorities, deepening decentralisation and administrative modernisation; but also ongoing challenges in deepening the deliberative quality of PBs, citizen's education and the institutionalisation of participants' power.
Keywords: 330; Participatory budgeting; governance; democratization; spatial justice; local governments